Tea Polyphenol Attenuates Oxidative Stress-Induced Degeneration of Intervertebral Discs by Regulating the Keap1/Nrf2/ARE Pathway. (9th January 2021) - Song, Dawei; Ge, Jun; Wang, Yingjie; Yan, Qi; Wu, Cenhao; Yu, Hao; Yang, Ming; Yang, Huilin; Zou, Jun
Abstract : Objective . Intervertebral disc degeneration (IDD) and low back pain caused by IDD have attracted public attention owing to their extremely high incidence and disability rate. Oxidative stress is a major cause of IDD. Tea polyphenols (TP) are natural-derived antioxidants extracted from tea leaves. This study explored the protective role of TP on the nucleus pulposus cells (NPCs) of intervertebral discs and their underlying mechanism. Methods . An in vitro model of H2 O2 -induced degeneration of NPCs was established. RT-qPCR and western blotting were used to detect the mRNA and protein expression of the targets. An in vivo model of IDD was established via acupuncture of the intervertebral disc. Radiological imaging and histological staining were performed to evaluate the protective role of TP. Results . H2 O2 contributed to NPC degeneration by inducing high levels of oxidative stress. TP treatment effectively increased the expression of nucleus pulposus matrix-associated genes and reduced the expression of degeneration factors. Further mechanistic studies showed that TP delayed H2 O2 -mediated NPC degeneration by activating the Keap1/Nrf2/ARE pathway . In vivo experiments showed that TP delayed the degeneration of NPCs in rats through the Keap1/Nrf2/ARE pathway. Conclusion . Our study confirmed that TP activates the Keap1/Nrf2/ARE pathway to exert an antioxidative stress role, ultimately delaying the degeneration of intervertebral discs.